Development And Evaluation Of Gluten-Free Rice Bread Formulated With Hydrocolloid-Protein Additive Systems - Mensah, P.O.; Tutu, C.O.; Akonor, P.A.; Bempah, J.O.; Asiedu, B.K.; Adusei, H.O.; Saalia, F.K. (Food and Humanity, 2025)
The structural and sensory limitations of gluten-free bread remain a major challenge in baking, particularly in formulations based on rice flour. This study explored the effects of xanthan gum, egg powder and gelatin powder, both individually and in combination, on the rheological behaviour, structural quality and sensory acceptability of gluten-free rice bread. Five formulations (F1-F5) were developed, with F1 serving as the control. Key quality parameters, thus, including dough firmness, adhesiveness, cohesiveness, loaf volume, specific volume, bread density, moisture content, crumb texture, crust appearance and sensory attributes, were evaluated. The formulation containing all three additives (F5) exhibited the best performance across nearly all metrics. F5 recorded the highest loaf volume (1295.7 ± 21.8 cm³), the lowest bread density (0.48 ± 0.02 g/cm³), the highest moisture content (36.8 ± 0.5 %) and the most preferred crust appearance (L* value = 42.3 ± 1.1; score = 8.0 ± 0.4). Rheological properties also showed significant enhancement, with F5 displaying the highest dough firmness (275.3 ± 4.2 g) and cohesiveness (93.1 ± 2.6). Principal Component Analysis (PCA) revealed strong positive correlations between F5 and key quality indicators such as crumb texture, overall acceptability and consistency. Mechanistic interpretation suggested that xanthan gum improved dough viscosity and water retention, egg powder contributed protein coagulation during baking and gelatin enhanced elasticity and moisture stabilisation. These synergistic effects resulted in gluten-free bread with structural, sensory and visual characteristics that closely approximate wheat-based bread. The results provide a strong formulation strategy for producing high-quality gluten-free bread with improved consumer appeal and functionality
Research Article
Keywords: Gluten-free bread; Rice flour; Xanthan gum; Egg powder; Gelatin; Dough rheology; Bread structure; Sensory evaluation